1)-x=4(6+x)
2)9(x+7)=-x
3)5(x-3)=4x
4)4(x+6)=x

1)-x=4(6+x)
2)9(x+7)=-x
3)5(x-3)=4x
4)4(x+6)=x

Срочно плиииииз

  • -х=4(6+х)
    -х=24+4х
    -х-4х=24
    -5х=24
    -х=24:5
    -х=4,8

    9(х+7)=-х
    9х+63=-х
    9х+х=-63
    10х=-63
    х=-63:(-10)
    х=6,3

    5(х-3)=4х
    5х-15=4х
    5х-4х=15
    х=15

    4(х+6)=х
    4х+24=х
    4х-х=-24
    3х=-24
    х=-24:(-3)
    х=-8

Добавить комментарий

Ваш e-mail не будет опубликован. Обязательные поля помечены *

Вы можете использовать эти HTMLтеги и атрибуты:

<a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <s> <strike> <strong>

79 − = 76